Heart Failure Risk Predictions and Prognostic Factors in Adults With Congenital Heart Diseases - Leczycki, Patryk; Banach, Maciej; Maciejewski, Marek; Bielecka-Dabrowa, Agata (Frontiers in Cardiovascular Medicine, 2022)
In recent decades the number of adults with congenital heart diseases (ACHD) has increased significantly. This entails the need for scrupulous evaluation of the current condition of these patients. The ACHD population is one of the most challenging in contemporary medicine, especially as well-known scales such as the NYHA classification have very limited application. At the moment, there is a lack of universal parameters or scales on the basis of which we can easily capture the moment of deterioration of our ACHD patients' condition. Hence it is crucial to identify factors that are widely available, cheap and easy to use. There are studies showing more and more potential prognostic factors that may be of use in clinical practice: thorough assessment with echocardiography and magnetic resonance imaging (e.g., anatomy, ventricular function, longitudinal strain, shunt lesions, valvular defects, pericardial effusion, and pulmonary hypertension), cardiopulmonary exercise testing (e.g., peak oxygen uptake, ventilatory efficiency, chronotropic incompetence, and saturation) and biomarkers (e.g., N-terminal pro-brain type natriuretic peptide, growth-differentiation factor 15, high-sensitivity troponin T, red cell distribution width, galectin-3, angiopoietin-2, asymmetrical dimethylarginine, and high-sensitivity C-reactive protein). Some of them are very promising, but more research is needed to create a specific panel on the basis of which we will be able to assess patients with specific congenital heart diseases.